A Single Chamber Direct Methanol Fuel Cell. Issue 21 (10th August 2017) - Thimmappa, Ravikumar; Aralekallu, Shambhulinga; Devendrachari, Mruthyunjayachari Chattanahalli; Kottaichamy, Alagar Raja; Bhat, Zahid Manzoor; Shafi, Shahid Pottachola; Lokesh, Koodlur Sannegowda; Thotiyl, Musthafa Ottakam
Abstract: The complexities associated with H2 storage project liquid fed direct alcohol fuel cells promising alternative to H2 ‐O2 fuel cells. However on the benchmark Pt‐based electrocatalytic interface, the multielectron alcohol oxidation kinetics proceed through a parallel pathway mechanism with CO intermediacy, demanding heavy loading of Pt‐based catalysts and an expensive Nafion‐based membrane. In a sagacious approach by altering the interfacial chemistry at the cathode electrolyte interface, this study shows a single chamber direct methanol fuel cell (DMFC) with a Pt‐free cathode and a freely diffusing electron acceptor (DEA). The positive redox energy of DEA assisted interfacial methanol oxidation kinetics by chemically unblocking CO poison from the Pt anode catalytic interface while simultaneously bestowing it with inherent electron accepting capability on methanol passive carbon cathode interface, guiding toward a membraneless configuration. In situ Fourier transform infrared (FTIR) spectroelectrochemical studies reveal the methanol oxidation in this membraneless configuration is driven by DEA predominantly in the direct CO‐free pathway, with ≈6 times amplification in fuel cell performance metrics than conventional Pt‐based DMFC. Abstract : Direct methanol fuel cell equipped with a powerful oxidant and alcohol passive carbon nanoparticle cathode can be designed in a membraneless configuration with the potential to power commercial electrical appliances.